Observability of surface currents in p-wave superconductors. (13th March 2017) - Bakurskiy, S V; Klenov, N V; Soloviev, I I; Kupriyanov, M Yu; Golubov, A A
Abstract: A general approach is formulated to describe spontaneous surface current distribution in a chiral p-wave superconductor. We use the quasiclassical Eilenberger formalism in the Ricatti parametrization to describe various types of the superconductor surface, including arbitrary roughness and metallic behavior of the surface layer. We calculate angle resolved distributions of the spontaneous surface currents and formulate the conditions of their observability. We argue that local measurements of these currents by muon spin rotation technique may provide an information on the underlying pairing symmetry in the bulk superconductor.